2021
DOI: 10.1101/2021.07.20.21260647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA Vaccine Effectiveness against COVID-19 among Symptomatic Outpatients Aged ≥16 Years in the United States, February – May 2021

Abstract: Evaluations of vaccine effectiveness (VE) are important to monitor as COVID-19 vaccines are introduced in the general population. Research staff enrolled symptomatic participants seeking outpatient medical care for COVID-19-like illness or SARS-CoV-2 testing from a multisite network. VE was evaluated using the test-negative design. Among 236 SARS-CoV-2 nucleic acid amplification test-positive and 576 test-negative participants aged ≥16 years, VE of mRNA vaccines against COVID-19 was 91% (95% CI: 83-95) for ful… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This analysis includes four additional months of data compared with an earlier evaluation of COVID‐19 VE between February and May 2021. 3 Despite predominance of the Delta variant in the latter study period, 7 our findings show protection against laboratory‐confirmed symptomatic illness. A decline in VE point estimates in the latter period could be attributed to reduced protection against the Delta or a result of waning protection of the initial vaccination series.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This analysis includes four additional months of data compared with an earlier evaluation of COVID‐19 VE between February and May 2021. 3 Despite predominance of the Delta variant in the latter study period, 7 our findings show protection against laboratory‐confirmed symptomatic illness. A decline in VE point estimates in the latter period could be attributed to reduced protection against the Delta or a result of waning protection of the initial vaccination series.…”
Section: Discussionmentioning
confidence: 61%
“…Methods used for estimating VE against laboratory‐confirmed symptomatic SARS‐CoV‐2 infection or COVID‐19 among persons seeking medical care/testing for SARS‐CoV‐2 in Flu VE Network study sites have been previously described. 3 Briefly, research staff screened persons who sought outpatient medical care (i.e., telehealth, primary care, urgent care, and/or emergency department) or clinical SARS‐CoV‐2 testing using a standard case‐definition for COVID‐like illness that included onset of fever/feverishness, cough, or loss of taste/smell with symptom duration <10 days. 4 Research staff contacted potentially eligible outpatients in person, by telephone, or email to confirm eligibility and enroll participants who consented verbally or in writing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Misclassification of exposure is a possibility as vaccination status was self-reported and dates of vaccination were not collected. However, other studies have shown very high agreement between self-reported and recorded COVID-19 vaccination status 67,68 . VE after one dose of mRNA vaccines is likely underestimated in this study because it was not known if the outcome occurred more than 15 days after the first dose.…”
Section: Discussionmentioning
confidence: 87%